2008
DOI: 10.1128/aac.01035-07
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Water Molecules Stabilize the Ω-Loop in Class A β-Lactamases

Abstract: A set of 49 high-resolution (<2.2 Å) structures of the TEM, SHV, and CTX-M class A ␤-lactamase families was systematically analyzed to investigate the role of conserved water molecules in the stabilization of the ⍀-loop. Overall, 13 water molecules were found to be conserved in at least 45 structures, including two water positions which were found to be conserved in all structures. Of the 13 conserved water molecules, 6 are located at the ⍀-loop, forming a dense cluster with hydrogen bonds to residues at the ⍀… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…OXA enzymes belong to the Class D group of β-lactamases and are known to be present in a number of bacteria [43]. SHV, TEM, and CTX-M enzymes belong to Ambler class A and were initially reported as plasmid borne in gram-positive bacteria [44]. More than 200 types of well characterized β-lactamases enzymes have been reported [45] and several attempts have been made to categorize them since the late 1960s [46][49].…”
Section: Resultsmentioning
confidence: 99%
“…OXA enzymes belong to the Class D group of β-lactamases and are known to be present in a number of bacteria [43]. SHV, TEM, and CTX-M enzymes belong to Ambler class A and were initially reported as plasmid borne in gram-positive bacteria [44]. More than 200 types of well characterized β-lactamases enzymes have been reported [45] and several attempts have been made to categorize them since the late 1960s [46][49].…”
Section: Resultsmentioning
confidence: 99%
“…For water activities below a critical water activity (a w = 0.5 for CALB) water initially binds to well-defined water-binding sites at the protein surface, [25,31] and then gradually a spanning water network is formed. [33,39,50] The amount of protein-bound water increased linearly with water activity, depending on the number of water-binding sites on the surface and their affinity toward water.…”
Section: Discussionmentioning
confidence: 99%
“…[28] Comparative studies of crystal structures showed that there are water binding sites on the surface and on the interior of a protein, which are occupied by water molecules in different crystal structures. [29][30][31] Computer simulations of enzymes in different solvents are a valuable tool for investigating the effect of solvent on the structure and dynamics of proteins. [21,32,33] While in most simulations proteins showed no significant structural changes in different solvents, the molecular flexibility decreased when simulated in organic solvents, [33,34] which has been confirmed by different experimental techniques, such as time-resolved fluorescence anisotropy [35] and dielectric relaxation spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…In continuation of this, conserved water molecules were determined between the blades of hemopexins from seeds. It seems they act as structural glue to tether one blade to the next by maintaining the overall tertiary structure as they function between the Ω loop and the rest of the class A β-lactamase protein structure 34 . During comparison of channels of DC25, CP4, LS24 and CAL, it was found that DC25 consists of only water molecules unlike ions.…”
Section: Discussionmentioning
confidence: 99%